The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5152/tjg.2015.0152
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET CT as a prognostic factor in hepatocellular carcinoma

Abstract: Background/Aims: To elucidate the role of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…The stage incorporation and analysis was weakly associated with outcome, so the multivariate analysis included significant components of this staging system that had stronger associations with outcome on UVA ( i.e ., ECOG Performance status, extrahepatic disease, and tumor burden) (Table 3). Despite these limitations, our results were in line with other studies that found a similar prognostic benefit to pre-treatment FDG-PET/CT scans in patients getting treated for HCC[16-22]. …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The stage incorporation and analysis was weakly associated with outcome, so the multivariate analysis included significant components of this staging system that had stronger associations with outcome on UVA ( i.e ., ECOG Performance status, extrahepatic disease, and tumor burden) (Table 3). Despite these limitations, our results were in line with other studies that found a similar prognostic benefit to pre-treatment FDG-PET/CT scans in patients getting treated for HCC[16-22]. …”
Section: Discussionsupporting
confidence: 91%
“…The role of FDG-PET in the assessment of different treatment modalities for HCC has been described in several reports[16-22]. Pant et al[17] assessed pre-treatment FDG-avidity as a prognostic index in the management of HCC in 100 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pode-se monitorar de forma não invasiva a instalação e progressão do CHC, quantificando a carga tumoral, identificando sítios metastáticos e quantificando a resposta ao tratamento por uma droga em teste (74) . (74,(83)(84)(85)(86)(87)(88) . Isto também foi visto na linhagem celular de CHC, pois a ausência da expressão da p53 levou a maior captação do 18 F-FDG, sendo portanto indicativo de pior prognóstico (80) .…”
Section: Pet E Chcunclassified